Epilepsy in Children with Tuberous Sclerosis Complex: A Prospective Observational Study in Bangladesh - Rahman, Md Mizanur (J Epilepsy Res, 2020)
BACKGROUND AND PURPOSE: Epilepsy is an important neurologic feature of patients with tuberous sclerosis complex (TSC). Most common seizure types are focal seizure and epileptic spasm. Seizure control often requires multiple antiepileptic drugs. This study has been done to evaluate the seizure types, electro-encephalography (EEG), neuroimaging features, and drug treatment of epilepsy in TSC. METHODS: This prospective observational study has been conducted on epilepsy patients with TSC at Bangabandhu Sheikh Mujib Medical University from 2011 to 2019. RESULTS: Seventy patients with a mean±standard deviation age of 5.64±3.96 years were identified and 57.1% were female. Most common type of seizure was focal seizure (46%). Epileptic spasm occurred in 17% of patients and all of them had seizure onset before 1 year. In 47% of patients EEG showed focal epileptic discharge; hypsarrhythmia was found in most of the patients with epileptic spasm. Majority of the patients needed more than one drug to control seizure. Only 34% of patients were seizure free for at least 12 months and 22.8% had drug resistant epilepsy. CONCLUSIONS: This study highlights the pattern of seizure, treatment pattern, response to drug, and short-time outcome of children with TSC with epilepsy in a developing country like Bangladesh.